Animal illustration : the essential reference - Grafton, Carol Belanger (Mineola, New York : Dover Publications, Inc., 2016)
"Comprehensive and entertaining, this volume comprises the greatest works in animal illustration from the Middle Ages through the twentieth century. The chronological presentation of hundreds of black-and-white and color images begins with medieval illuminated manuscripts and the Renaissance works of Konrad Gesner and other woodcut illustrators from the first centuries of printing. Subsequent illustrations include the seventeenth-century real and imaginary animals of Matthaus Merian and the eighteenth-century compilations of Albertus Seba. Nineteenth-century images are drawn from sources as diverse as J. G. Heck's Bilder Atlas; the prints of George Baron Cuvier; William Jardine's 40-volume TheNaturalist's Library; bird illustrations by John James Audubon, Thomas Bewick, Edward Lear, and many others; and butterfly illustrations and other graphics by the anonymous creators of Victorian die cuts. The exquisite Edwardian bestiary of the Detmold brothers brings the collection into the twentieth century. Detailed bibliographical information concerning every source and biographical information on the artists make this volume a vital reference tool as well as a splendid resource of outstanding animal illustrations. Students of graphic art, typography, and illustration as well as graphic designers and advertising professionals will prize this treasury of material from many rare historic sources"--
Keywords: Animals in art -- Pictorial works